المرابحة في المصارف الإسلامية: دراسة فقهية Murabaha in Islamic banks: A Fiqhi study - Abdulkadir, Ahmad (International Journal of Al-Turath In Islamic Wealth and Finance, 2020)
تحتل المرابحة مكانة سامية من بين سائر أنواع المعاملات المصرفية، لذا فإن البحث يهدف إلى بيان فقه المرابحة المصرفية من حيث بيان مفهوم المرابحة ومشروعيتها وأركانها وصورها. كما يهدف إلى بيان حكم المرابحة المصرفية وماهيتها، وتوضيح نسبة التمويل بالمرابحة في المصارف الإسلامية، وبيان عمليات المرابحة الخارجية لأجل الاستيراد. ولقد استخدم الباحث المنهج الاستقرائي والتحليلي، من حيث ذكر جزئيات المرابحة، ثم تعقيب ذلك بالشرح والتحليل لكل جزء من مفرداتها. توصلت الدراسة إلى أن الإلمام بنسبة التمويل بالمرابحة في المصارف الإسلامية تتجلى أهميته في بيان نطاق استخدام المرابحة في المصارف الإسلامية. كما استنتج البحث بأن بيع المرابحة يقوم على أصلين: الأول: ذكر الثمن الأصلي، والثاني: طلب زيادة ربح معلوم، وهذا هو القاسم المشترَك بين المذاهب الأربعة في تعريفاتهم للمرابحة. ويستخلص أيضا أن الدكتور سامي حمود استند في إجازته للمرابحة للآمر بالشراء على ما ذكره الإمام الشافعي في الأم بخصوص الصورة الثانية للمرابحة. كما تبيّن بأن المرابحة الفقهية تتفق مع المرابحة المصرفية في تحديد الثمن الأصلي، وكذلك الاتفاق على الربح المعلوم لدى الجميع. الكلمات المفتاحية: المرابحة الفقهية، الضوابط، المرابحة المصرفية، المصارف الإسلامية، العميل. Abstract Murabahah has a significant role as a financial contracts compared to other types of banking transactions. This research aims to clarify the jurisprudential matters pertaining to Murabahah as used in the banking sector, particularly on the concept of Murabahah, its legitimacy, pillars and types. It also discusses the rules and the nature of Murabahah and the percentage of its usage in Islamic banks. In completing this research, the researcher used inductive and analytical methods. This study concluded that the percentage of usage relating to Murabahah financing in Islamic banks is evident as practical tools. The research also concluded that Murabahah contract is based on two principles i.e. (i) mentioning the original price (cost), and (ii) profit margin. These are common denominators in definitions of Murabahah as provided by the four schools of legal thought. It is also found that the concept of Murabahah as discussed by Dr. Sami Hamoud is based on what Imam Al-Shafi’i mentioned in his prominent book of Fiqh titled “Al Umm”. It is agreed among Muslim jurists regarding the principles of original price plus profit for Murabahah financing. Keywords: Fiqh Murabaha, Rules, Banking Murabaha, Islamic banks, Customer.